Students' perception of the contribution of UiTM Kelantan activities in preparing for quality graduates / Tuan Mohd Rosli Tuan Hassan, Dr Asry Yusoff and Cheam Chai Li - Tuan Hassan, Tuan Mohd Rosli; Yusoff, Asry; Chai Li, Cheam (2005)
One of UiTM missions is to produce quality graduates to meet the country's manpower needs to support economic development and growth. However, with the academic and non-academic programs and activities being provided by UiTM Kelantan so far, we do not know to what extend the institution manages to produce quality students. Therefore, the perception from a total of 336 UiTM Kelantan graduating or finals semester students ( May 2 003) from diploma 1 levels ( DBS, D IB, CS, AC, AD and IS) way up to degree programs (namely Marketing and Finance) are evaluated to reveal some insights to the problems. The independent variables in this study are UiTM Kelantan (HEA and HEP) programs and campus environment. Primary data were collected via questionnaires and focus group interviews. Person correlation, multiple regression and moderated regression analysis show that students perceived the UiTM program and the campus environment have a very weak, influence or impact on their personality development and academic performance. They also perceived that their personal and family background do not enhance the relationship between the UiTM program and the campus environment with either personality development or academic performance. The qualitative findings seems to be quite parallel with the quantitative method when it is revealed that the students have conflicting views on the influence of the UiTM program and campus environment, whether positive or otherwise, on their academic performance and personality development along the years 1999 to 2003.